The status of neonatal screening in China, 2013. (June 2016) - Zhong, Kun; Wang, Wei; He, Falin; Wang, Zhiguo
Objectives: To investigate the status of neonatal screening in China in 2013. Method: All Chinese neonatal screening laboratories were asked to submit information about the number of newborns screened and for which diseases, the rate of acceptable blood spots, and the time between sample collection and delivery to laboratories and reporting. Results: Of the 202 laboratories, 194 (96%) submitted data. In 2013, 73.6% (142/193) of laboratories testing for phenylketonuria (PKU), 72.7% (141/194) for congenital hypothyroidism (CH), 58.9% (43/73) for glucose-6-phosphate dehydrogenase (G6PD) deficiency and 53.1% (34/64) for congenital adrenal hyperplasia (CAH) screened more than 30, 000 newborns. The incidences of PKU, CH, G6PD deficiency, and CAH were 1:12189, 1:2281, 1:44 and 1:6084, respectively. The estimated coverage of screening for PKU, CH, G6PD deficiency, and CAH were 86.3 ∼ 87.5%, 87.9 ∼ 89.1%, 24.0 ∼ 25.0% and 18.9% ∼ 19.9%, respectively. The rates of acceptable blood spots were ≥98% in 161 (87.0%) of 185 laboratories. More than half the laboratories could not achieve a time from collection to reporting of 5 days. Conclusion: Neonatal screening has developed rapidly in China but the biggest challenge is still to increase coverage and expand the screening disease panel across the entire country. More government support is needed to make neonatal screening more efficient.